Variable organization of symbiont-containing tissue across planthoppers hosting different heritable endosymbionts - Michalik, Anna; Franco, Diego Castillo; Deng, Junchen; Szklarzewicz, Teresa; Stroiński, Adam; Kobiałka, Michał; Łukasik, Piotr (Frontiers in Physiology, 2023)
Sap-feeding hemipteran insects live in associations with diverse heritable symbiotic microorganisms (bacteria and fungi) that provide essential nutrients deficient in their hosts’ diets. These symbionts typically reside in highly specialized organs called bacteriomes (with bacterial symbionts) or mycetomes (with fungal symbionts). The organization of these organs varies between insect clades that are ancestrally associated with different microbes. As these symbioses evolve and additional microorganisms complement or replace the ancient associates, the organization of the symbiont-containing tissue becomes even more variable. Planthoppers (Hemiptera: Fulgoromorpha) are ancestrally associated with bacterial symbionts Sulcia and Vidania, but in many of the planthopper lineages, these symbionts are now accompanied or have been replaced by other heritable bacteria (e.g., Sodalis, Arsenophonus, Purcelliella) or fungi. We know the identity of many of these microbes, but the symbiont distribution within the host tissues and the bacteriome organization have not been systematically studied using modern microscopy techniques. Here, we combine light, fluorescence, and transmission electron microscopy with phylogenomic data to compare symbiont tissue distributions and the bacteriome organization across planthoppers representing 15 families. We identify and describe seven primary types of symbiont localization and seven types of the organization of the bacteriome. We show that Sulcia and Vidania, when present, occupy distinct bacteriomes distributed within the body cavity. The more recently acquired gammaproteobacterial and fungal symbionts generally occupy separate groups of cells organized into distinct bacteriomes or mycetomes, distinct from those with Sulcia and Vidania. They can also be localized in the cytoplasm of fat body cells. Alphaproteobacterial symbionts colonize a wider range of host body habitats: Asaia-like symbionts often colonize the host gut lumen, whereas Wolbachia and Rickettsia are usually scattered across insect tissues and cell types, including cells containing other symbionts, bacteriome sheath, fat body cells, gut epithelium, as well as hemolymph. However, there are exceptions, including Gammaproteobacteria that share bacteriome with Vidania, or Alphaproteobacteria that colonize Sulcia cells. We discuss how planthopper symbiont localization correlates with their acquisition and replacement patterns and the symbionts' likely functions. We also discuss the evolutionary consequences, constraints, and significance of these findings.